Pengaruh Long Term Debt to Equity Ratio, Gross Profit Margin, Net Profit Margin dan Return On Asset Terhadap Pertumbuhan Laba (Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2021-2022) - Choiroh, Ni’matin; Purbowati, Rachyu (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
Profitability is measured in large part by how quickly it is growing over time. Profit growth from one year to the next is a key performance indicator for practically every firm, as it demonstrates the company's capacity to create revenue and advance its mission. This study aims to answer the question of whether or not the Long Term Debt to Equity Ratio, Gross Profit Margin, Net Profit Margin, and Return On Assets of food and beverage manufacturing companies listed on the Indonesia Stock Exchange affect their profit growth in the years 2021 and 2022). Purposive sampling was used for this study's data collection. The information used is secondary data, namely the sampled companies' financial statements for the years 2021 and 2022 in the food and beverage production industry. Data in this study was analyzed using a quantitative approach, which included descriptive analysis, tests of classical assumptions, multiple linear regression analysis, and hypothesis testing. Long-term debt to equity ratio, Gross Profit Margin, and Net Profit Margin were tested as independent factors, and they were found to have no significant effect on profit expansion. Nonetheless, the rate at which profits expand is affected by the independent variable Return On Assets.